ChemInform Abstract: Adsorption, Intrusion and Freezing in Porous Silica: The View from the Nanoscale. Issue 29 (1st July 2013) - Coasne, Benoit; Galarneau, Anne; Pellenq, Roland J. M.; Di Renzo, Francesco
Abstract: Review: molecular simulation and theory and freezing in porous silica; 271 refs.